2013
DOI: 10.1007/s10803-013-1813-z
|View full text |Cite
|
Sign up to set email alerts
|

Challenging Stereotypes: Sexual Functioning of Single Adults with High Functioning Autism Spectrum Disorder

Abstract: This study examined the sexual functioning of single adults (61 men, 68 women) with high functioning autism and Asperger syndrome living in the community with and without prior relationship experience. Participants completed an on-line questionnaire assessing autism symptoms, psychological functioning, and various aspects of sexual functioning. In general participants reported positive sexual functioning. Participants without prior relationship experience were significantly younger and more likely to be male a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
106
2
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(123 citation statements)
references
References 43 publications
11
106
2
4
Order By: Relevance
“…Most studies on sexuality in individuals with ASD, as in the case of the general population, focus on the prevalence of sexual behaviours and on sexual knowledge (Dewinter et al, 2013;Kellaher, 2015). Studies based on self-report (Byers et al, 2012(Byers et al, , 2013Dewinter et al, 2015;Mehzabin and Stokes, 2011;Ousley and Mesibov, 1991) and parental or caregiver reports (Haracopos and Pedersen, n.d.;Hellemans et al, 2007Hellemans et al, , 2010Holmes and Himle, 2014;Stokes and Kaur, 2005) have shown that sexuality is a part of life for individuals with ASD. Especially highfunctioning adolescents and adults with ASD reported or demonstrated interest in relationships and partnered sexuality (Haracopos and Pedersen, n.d.).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on sexuality in individuals with ASD, as in the case of the general population, focus on the prevalence of sexual behaviours and on sexual knowledge (Dewinter et al, 2013;Kellaher, 2015). Studies based on self-report (Byers et al, 2012(Byers et al, , 2013Dewinter et al, 2015;Mehzabin and Stokes, 2011;Ousley and Mesibov, 1991) and parental or caregiver reports (Haracopos and Pedersen, n.d.;Hellemans et al, 2007Hellemans et al, , 2010Holmes and Himle, 2014;Stokes and Kaur, 2005) have shown that sexuality is a part of life for individuals with ASD. Especially highfunctioning adolescents and adults with ASD reported or demonstrated interest in relationships and partnered sexuality (Haracopos and Pedersen, n.d.).…”
Section: Introductionmentioning
confidence: 99%
“…Hellemans et al 2007;Stokes and Kaur 2005). Although some studies have found average psychosexual knowledge levels in individuals with ASD whom are cognitively able (Byers et al 2013), such differences may be explained to the diverse operationalization of psychosexual knowledge, ranging from simple theoretical vocabulary knowledge (e.g. what is a 'wet dream') to broader psychosexual knowledge, such as knowledge on developing relationships (see Dewinter et al 2013 for a comprehensive review).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many high-functioning individuals with ASD have engaged in sex with men and women (Byers, Nichols, & Voyer, 2013;Hellemans, Colson, Verbraeken, Vermeiren, & Deboutte, 2007) and developed romantic relationships (Strunz et al, 2017); the proportion of them who marry has been reported as 10% (Yukawa et al, 2013) to 16% (Tani et al, 2012). There are increasing opportunities for ASD individuals to get married; that means there are challenges for ASD individuals in maintaining long-term relationships and marrying (Howlin, Mawhood, & Rutter, 2000;Orsmond, Krauss, & Seltzer, 2004;Renty & Roeyers, 2007).…”
Section: Introductionmentioning
confidence: 99%